2021
DOI: 10.1029/2020jb020735
|View full text |Cite
|
Sign up to set email alerts
|

Mantle Heterogeneity and Melting Processes in the South China Sea: Thermal and Melting Models Constrained by Oceanic Crustal Thickness and Basalt Geochemistry

Abstract: The South China Sea (SCS) is one of the largest marginal seas in the western Pacific and is located at the junction of the Eurasian, Philippine Sea, and Indo-Australian plates (Figure 1). The SCS can be divided into the northwest subbasin, east subbasin, and SW subbasin. Despite its relatively short evolution history, the SCS has undergone a series of tectonic and magmatic processes, including continental rifting and breakup, seafloor spreading, and subduction, together with extensive magmatism (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 102 publications
(305 reference statements)
0
2
0
Order By: Relevance
“…The MORBs of the East sub-basin (U1431) do not have unradiogenic Pb isotopic compositions and hence it has been suggested that the role of lower continental crust is insignificant here (Li et al, 2008;Pautot et al, 1986;Zhang et al, 2018Zhang et al, , 2021. Based on magnetic anomalies, it was inferred that the central East Sub-basin developed within a pre-existing ocean, whereas the Southwest sub-basin evolved from a continental rift and therefore had a more continental signature (Li et al, 2008).…”
Section: Ancient Cratonic Lower Continental Crustal Materials In the ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The MORBs of the East sub-basin (U1431) do not have unradiogenic Pb isotopic compositions and hence it has been suggested that the role of lower continental crust is insignificant here (Li et al, 2008;Pautot et al, 1986;Zhang et al, 2018Zhang et al, , 2021. Based on magnetic anomalies, it was inferred that the central East Sub-basin developed within a pre-existing ocean, whereas the Southwest sub-basin evolved from a continental rift and therefore had a more continental signature (Li et al, 2008).…”
Section: Ancient Cratonic Lower Continental Crustal Materials In the ...mentioning
confidence: 99%
“…As a continental marginal sea, the SCS has experienced the full Wilson Cycle including continental rifting and breakup, seafloor spreading and subduction (Ding et al, 2018;Li et al, 2015;Taylor & Hayes, 1983) and the upper mantle is proposed to be contaminated by delaminated lower continental crustal materials (Li et al, 2008;Pautot et al, 1986;Zhang et al, 2018Zhang et al, , 2021. Lower continental crustal materials are considered to have unradiogenic Pb isotopes (O'Nions et al, 1979).…”
Section: Ancient Cratonic Lower Continental Crustal Materials In the ...mentioning
confidence: 99%